The treasure house - Khan , Saniyasnain" (India, Goodword books, 2011)
Qarun was a man of immense wealth and pride. He attributed his riches solely to his own knowledge and efforts, neglecting to acknowledge Allah's blessings. When Prophet Musa advised him to be humble and share his wealth with those in need, Qarun refused and boasted about his treasures. As a consequence of his arrogance and ingratitude, Allah caused the earth to swallow both Qarun and his treasure house, serving as a lesson about the dangers of pride and the importance of humility and gratitude.